The memorization of epitomes in the Epicurean community and the redefinition of philosophical praxis (Revista Archai, 2017)
This paper aims to offer a critical reading of a widely favoured interpretation of Epicurean philosophy, which assumes, in broad terms, that Epicurean pedagogy consisted primarily in the practice of memorizing the doctrines included in the Epicurean epitomes. I will suggest, on the contrary, that there are good reasons to believe that Epicurean pedagogy had little to do with the image delivered by that line of interpretation. I will propose an alternative reading, which takes memorization practices off of the center of the stage and reintegrates the epitomes to the pedagogical dynamics that were peculiar to the Epicurean community.